The use of serodiagnosis in the retrospective investigation of a nursery outbreak associated with Escherichia coli O157:H7. Issue 7 (July 1998) - Cheasty, T; Robertson, R; Chart, H; Mannion, P; Syed, Q; Garvey, R; Rowe, B
Abstract : AIMS: To use serology to investigate an outbreak of verocytotoxin (VT) producing Escherichia coli O157 in a hospital nursery, following the detection of faecal E coli O157 (phage type 49) producing VT type 2. METHODS: ELISA and immunoblotting techniques, based on lipopolysaccharide (LPS) purified from E coli O157; diagnostic bacteriology; serotyping and phage typing; DNA probes for VT. RESULTS: 29 of 126 sera contained antibodies to the LPS of E coli O157: 10 were from children, three were from staff, and 11 were from hospital kitchen staff. Five parents of children attending the nursery were antibody positive. Sixty four sera from other hospital staff and controls did not contain antibodies to the LPS of E coli O157. CONCLUSIONS: Serology detected evidence of infection with E coli O157 in 23% of sera examined. By bacteriology alone, only a single case of infection with E coli O157 would have been detected. Serology is valuable in providing evidence of infection with E coli O157.